EFFECT OF MEDIUM COMPOSITION ON ENZYMATIC PROTEIN HYDROLYSIS IN HETEROGENEOUS SYSTEMS - Zakirova Muyassar Rakhimovna (Journal of new century innovations, 2023)
Abstract: At present, the use of enzyme preparations is an integral part of most industrial and agricultural processes.